Diversity of Fungi in the Mount Rinjani National Park Kembang Kuning Resort, Jeruk Manis Village, Sikur District, East Lombok Regency - Dzakwan Army Fawwaz; Tina Warasari; Ernawati; Yulia Nurhaliza; Yuni Sucitawati; Ervina Titi Jayanti; Baiq Muli Harisanti; Sri Nopita Primawati (Ecobios Journal Of Environmental Science, 2024)
Mount Rinjani National Park is one of the ecosystems with mountain rainforest and savanna types located on Lombok Island, West Nusa Tenggara with a variety of fungal diversity. This research was conducted in the Jeruk Manis area, this area is one of the many areas included in the Mount Rinjani National Park. This study aims to observe the diversity of fungi in the Mount Rinjani National Park area. The research was conducted from 08.00 - 10.00 WITA. The method used in this study is the exploration method. The exploration method is one method where researchers conduct direct exploration in the Jeruk Manis TNGR (Mount Rinjani National Park) area. Fungi are eukaryotic organisms that do not have chlorophyll, grow as hyphae, have cell walls containing chitin, are heterotrophic, absorb nutrients through their cell walls, excrete extracellular enzymes into the environment through spores, and reproduce sexually and asexually. Ganoderma lucidum, also known as reishi or lingzhi, is a fungus that has long been used in traditional medicine in Asia. Neofevolus alveolaris is a wood fungus that grows saprophytically in forests. Stereum hirsutum is a fungus that is usually found on dead wood in forests. Ramariopsis kunzei  is a fungus that has a body shape that resembles a cone-shaped mushroom with a yellow or orange color. Entoloma abortivum, also known as the "lobster mushroom", is a unique fungus because it is the result of parasitism on other fungi, namely Russula or Lactarius fungi. Baeospora myosura is a fungus that is usually found in forests, growing saprophytically on decaying organic matter such as leaf litter or dead wood.